Update Review and Clinical Presentation in Congenital Insensitivity to Pain and Anhidrosis - L. M. Pérez-López; M. Cabrera-González; D. Gutiérrez-de la Iglesia; S. Ricart; G. Knörr-Giménez (Case Reports in Pediatrics)
Introduction. Congenital insensitivity to pain and anhidrosis (CIPA) or hereditary sensory and autonomic neuropathy type IV is an extremely rare syndrome. Three clinical findings define the syndrome: insensitivity to pain, impossibility to sweat, and mental retardation. This pathology is caused by a genetic mutation in the NTRK1 gene, which encodes a tyrosine receptor (TrkA) for nerve growth factor (NGF). Methods. The consultation of a child female in our center with CIPA and a tibia fracture in pseudoarthrosis encouraged us to carefully review literature and examine the therapeutic possibilities. A thorough review of literature published in Pubmed was done about CIPA and other connected medical issues mentioned in the paper. Conclusions. The therapeutic approach of CIPA remains unclear. The preventive approach remains the only possible treatment of CIPA. We propose two new important concepts in the therapeutic approach for these patients: (1) early surgical treatment for long bone fractures to prevent pseudoarthrosis and to allow early weight bearing, decreasing the risk of further osteopenia, and (2) bisphosphonates to avoid the progression of osteopenia and to reduce the number of consecutive fractures.